Penerapan Sistem Informasi untuk Media Absensi Menggunakan QR Code - Suhartini Suhartini; Hadian Mandala Putra; Nurhidayati Nurhidayati (Infotek: Jurnal Informatika dan Teknologi, 2023)
Attendance is something that must be done by students. In the attendance process, SMPN 3 Terara still uses the manual method. Therefore, we need a student attendance system that can collect and store the data so that it can be processed quickly, efficiently and accurately. One of the technologies currently developing is QR Code, QR Code is very much needed because of its ability to store larger data so that it can provide fast and accurate services. One of the things that can be done to support the author in designing a QR Code Application for Media Student Attendance services for SMPN 3 Terara is using the Extreme Programming research method. The purpose of this research is to establish an attendance system so that the process will be more efficient and can be monitored easily by the teacher and by the academic department. The results of this study are a student attendance application that uses a QR code as a medium for student attendance input based on a local network which is implemented in order to create an attendance information system that provides convenience for students in the attendance process, reduces acts of cheating committed by students, and facilitates reports when making recaps report.